The distinctive determinants of European urban growth: Does one size fit all? - Paul C. Cheshire; Stefano Magrini (European Regional Science Association (ERSA), 2002)
This paper investigates growth differences in the urban system of the EU12. Alternative dependent variables - growth in population and real GDP per capita - are analysed and instructive differences emerge. The US model which assumes perfect factor mobility does not seem well adapted to European conditions. There is evidence strongly suggesting that equilibrating flows between cities are highly constrained in the EU. Models in which growth of real GDP p.c. are the dependent variable perform well and make it possible to test significant hypotheses. Evidence is found which is supportive of a spatial adaptation of the endogenous growth model with the relative size of the university sector having a highly significant role in explaining growth differences. In addition the analysis supports the conclusion that systems of urban governance are strongly related to growth. The variables are formulated in a way which tests hypotheses derived from 'fiscal federalism' viewing growth promotion as the production of a local public good. While international factor flows appear to be constrained as an adjustment mechanism the density of urbanisation in regions of the EU12 seems to produce a strong local 'growth shadow' effect consistent with commuting flows having an important role in spatial economic adjustment processes. Finally new evidence is found supporting the conclusion that integration shocks in the EU favour core areas but that this effect tends to fade with time.
Keywords: 330